Problems of Applying Film Coatings During Scale-up Technology - A. V. Strelkova; E. V. Flisyuk (Разработка и регистрация лекарственных средств, 2022)
Introduction. Technology transfer is an integral part of the life cycle of any drug. The coating is a critical step in the production of coated tablets. The transfer of the film coating application process is often accompanied by the rejection of a part of the drug series due to various defects in the target surface.Aim. To classify the types of defects formed at the stage of “Application of the film shell” in the devices of the “Coater” drum type, to identify the causes of occurrence, to develop ways to eliminate these defects.Materials and methods. Film-coated tablets with INN diosmin, sildenafil, dipyridamole, atorvastatin, rosuvastatin as the object of the study were selected. The samples were obtained on a single-punch tablet press EP-1 (ERWEKA GmbH, Germany) and coated with a film shell in a coating unit of the type "copper" BGB-1 (Chongqing Jinggong Pharmaceutical Machinery Co., Ltd., China).Results and discussion. Appearance defects are classified according to the degree of criticality: critical (influx, chipping, recess, rupture, delamination, breaking, rubbing, sticking, pigmentation, discoloration, scratches, crack), significant (build-up, inclusion), minor defect. The main causes of the defect have been established: the property of the core tablet (for example, poor adhesive properties, hydrophobicity), technological parameters of the process (the speed of rotation of the drum, the speed of spraying, the pressure on the spray, the pressure on the formation of the torch, the temperature of the incoming air. The main consequences of the occurrence of each type of defect are considered, among which are insignificant (not affecting the quality) and critical (affecting the quality indicators of "dissolution").Conclusion. In the course of the study, the types of critical and significant defects, the causes of occurrence and ways to eliminate these defects are considered.